(3ChQGb GdCShGb GdeGdjI Hjf GdeVGQHI hGdESJKeGQ hJLGQI GdeTJbGJ hJMQjQ GdCShGb (B:s (3OQGSI hGbYjI ddCReI GdeGdjI GdYGdejI (B/s - (3QVhGf, SejQ YHO GdMejOs ((3GdbGgQI(B: s (3GfGQ GdfTQ ddLGeYGJ(B, s, 2009)
(3Shb GdChQGb GdeGdjI(B((3GdeaGgje(B- (3GdhXGFa(B-(3eYGjjQ GdcaGAI(B)(3, WQb hCSGdjH JfajP GdYedjGJ aj eNJda GdHhQUGJ hGdbhGfjf GdMGceI ddJYGed aj HYV GdCShGb, hLhg GdNdGa Hjf GdeVGQHI hGdESJKeGQ, GdCReI GdeGdjI GdYGdejIs
(3GdeQGLY U(B.205s
Keywords: (3GdCReI GdeGdjI GdYGdejIs; (3GdESJKeGQs; (3GdChQGb GdeGdjIs; (3GdHhQUGJs